Genetic variability studies for quality traits in rapeseed-mustard (Journal of Oilseed Brassica, 2026)
Brassica oil is the world’s third most important sources of edible vegetable oils diet, since they provide energy, improve taste, palatability of food. The fatty acid composition of oil is extremely important as the presence or absence of different fatty acids and their relative amounts determine the nutritional quality of the oil. The present study was carried out in the biochemistry laboratory of ICAR-DRMR, Bharartpur during 2015- 16 for the fatty acid profiling with the wield of Gas Chromatography using twenty five advanced breeding lines of Gobhi Sarson (Brassica napus L.) and three released varieties of brown sarson (B. rapa var. Brown Sarson). All the genotypes were genetically maintained at MRCFC, Khudwani, SKUAST-Kashmir, India. The results have revealed that the oleic acid in the 28 genotypes ranged from 22.58 to 56.67%, while as the linoleic & linolenic acid ranged from 16.63 to 29.05 % and 4.58 to 26.76 respectively. The erucic acid an anti-nutritional factor also showed wide range and the study has identified genotypes KGS-8, KGS-10, KGS-36 and KGS-40 for low erucic acid (less than 2 percent). KGS-10 was identified for the canola type as the said genotype contained the erucic acid of 1.99% & glucosinolate content of 26.3 ìmole per gram in the defatted meal (double zero).The study has further revealed that the erucic acid showed significantly high, but negative correlation with oleic acid (-0.92), linoleic acid (-0.83) and linolenic acid (-0.52), whileas significant and positive correlation was observed with Palmitic+Stearic acid (0.03) and glucosinolate content (0.16).The considerable genetic variation and high heritability for different fatty acid composition suggested that selection for improving some of the fatty acid composition would be promising in the future breeding programme.